2013
DOI: 10.1088/0004-637x/768/2/187
|View full text |Cite
|
Sign up to set email alerts
|

A New Method of Pulse-Wise Spectral Analysis of Gamma-Ray Bursts

Abstract: Time-resolved spectral analysis, though a very promising method to understand the emission mechanism of gamma-ray bursts (GRBs), is difficult to implement in practice because of poor statistics. We present a new method for pulse-wise time-resolved spectral study of the individual pulses of GRBs, using the fact that many spectral parameters are either constants or smooth functions of time. We use this method for the two pulses of GRB 081221, the brightest GRB with separable pulses. We choose, from the literatur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 46 publications
0
24
1
Order By: Relevance
“…• The time-integrated spectrum during the bright phase (from 20s to 30s since the trigger) of GRB 081221 observed with Fermi/GBM has a broad plateau in the 15-180 keV band, and is well fitted by the mBB model, yielding the kT min = 4.4 ± 0.3 keV, kT max = 57.0 +1.6 −1.4 keV, m = −0.46 +0.05 −0.06 . • As for the time-resolved spectra, although the BB model is not the best-fit model when the whole burst is divided into 40 slices, we obtain acceptable fits with the single blackbody model (without the power-law component), which is simpler compared to the 2BB plus PL model of Basak & Rao (2013). The kT of the main burst increases rapidly from ∼ 9 keV to ∼ 20 keV.…”
Section: Discussionmentioning
confidence: 80%
“…• The time-integrated spectrum during the bright phase (from 20s to 30s since the trigger) of GRB 081221 observed with Fermi/GBM has a broad plateau in the 15-180 keV band, and is well fitted by the mBB model, yielding the kT min = 4.4 ± 0.3 keV, kT max = 57.0 +1.6 −1.4 keV, m = −0.46 +0.05 −0.06 . • As for the time-resolved spectra, although the BB model is not the best-fit model when the whole burst is divided into 40 slices, we obtain acceptable fits with the single blackbody model (without the power-law component), which is simpler compared to the 2BB plus PL model of Basak & Rao (2013). The kT of the main burst increases rapidly from ∼ 9 keV to ∼ 20 keV.…”
Section: Discussionmentioning
confidence: 80%
“…We have further shown that this model gives statistically better fit compared to the other models, when all the three GRBs are considered. Considering the fact that this model is also the preferred one for the bright GRBs with single/ separable pulses (Basak & Rao 2013), we can conclude that such a composite model needs to be examined for other GRBs too. This spectral description has several attractive features which can be used to constrain the GRB emission mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…(Liang & Kargatis 1996). However, it is known that the E peak evolution can be more complicated than the simple assumption of Basak & Rao (2012b)-there may be "intensity tracking" nature in the evolution (e.g., Ford et al 1995;Liang & Kargatis 1996;Kaneko et al 2006;Lu et al 2010;Hakkila & Preece 2011;Lu et al 2012;Basak & Rao 2013a;. Hence, in the present paper we restrict ourselves only to the pulse-wise Amati correlation.…”
Section: Data Selection and Analysismentioning
confidence: 98%